Advanced mean field methods : theory and practice - Opper, Manfred; Saad, David (Neural information processing series., 2001)
"Bringing together ideas and techniques from diverse disciplines, this book covers the theoretical foundations of advanced mean field methods, explores the relation between the different approaches, examines the quality of the approximation obtained, and demonstrates their application to various areas of probabilistic modeling."--Jacket